What interventions should we add to weight reducing diets in adults with obesity? A systematic review of randomized controlled trials of adding drug therapy, exercise, behaviour therapy or combinations of these interventions - Avenell, A; Brown, T.J; McGee, M.A; Campbell, M.K; Grant, A.M; Broom, J; Jung, R.T; Smith, W.C.S (Journal of human nutrition and dietetics, 2004)
Background  Evidence is needed for the effectiveness of interventions given with reducing diets for obese adults: drug therapy, exercise, or behaviour therapy. Methods  We systematically reviewed randomized controlled trials in any language. We searched 13 databases and handsearched journals. Trials lasted 1 year or more. One investigator extracted data and a second checked data extraction. Trial quality was assessed. Results  Adding orlistat to diet was associated with weight change for up to 24 months (−3.26 kg, 95% CI, −4.15 to −2.37 kg), and statistically significant beneficial changes were found for total and LDL cholesterol, blood pressure and glycaemic control. Adding sibutramine to diet was associated with a 12 month weight change of −4.18 kg (95% CI, −5.14 to −3.21 kg), and statistically significant beneficial effects on high density lipoprotein cholesterol (HDL) and triglycerides (TGs), but an increase in diastolic blood pressure. Adding exercise to diet, or to diet and behaviour therapy, was associated with improved weight loss for up to 36 months and improvements in HDL, TGs and blood pressure. Adding behaviour therapy to diet, or to diet and sibutramine together, was associated with improved weight loss for up to 18 months. Adding drugs, exercise or behaviour therapy to dietary advice was each associated with similar weight change. Conclusions  Adding orlistat, sibutramine, exercise, or behaviour modification to dietary advice can improve long‐term weight loss.